2021
DOI: 10.21203/rs.3.rs-634658/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hunger and Its Associated Factors in an Urban Cluster in the Western Brazilian Amazon: A Population-Based Study

Abstract: Background: Hunger affects millions of people worldwide. In the current pandemic scenario of COVID-19, Brazil experienced an epidemic peak of hunger, amplifying existing pre-pandemic vulnerabilities, mainly in the Northern Region of the Country. The aim of the present study was to investigate the prevalence of food insecurity and its associated factors in homes with children under five years of age in an urban cluster of a municipality of the Western Brazilian Amazon. Methods: A household survey was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, it is expected that due to the COVID-19 crisis and the absence of national child anthropometric surveys for 15 years, the current prevalence of childhood overweight has likely worsened [ 5 , 6 ]. In this context, the Brazilian Amazon was one of the most affected regions in the country due to its remote location and lack of specialized health assistance [ 5 , 7 ]. Recent studies revealed that approximately 70% of the northern population experience food insecurity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is expected that due to the COVID-19 crisis and the absence of national child anthropometric surveys for 15 years, the current prevalence of childhood overweight has likely worsened [ 5 , 6 ]. In this context, the Brazilian Amazon was one of the most affected regions in the country due to its remote location and lack of specialized health assistance [ 5 , 7 ]. Recent studies revealed that approximately 70% of the northern population experience food insecurity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%